2016
DOI: 10.1103/physrevlett.117.036602
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Effects in the Thermoelectric Power Factor of Low-Dimensional Semiconductors

Abstract: We theoretically investigate the interplay between the confinement length L and the thermal de Broglie wavelength Λ to optimize the thermoelectric power factor of semiconducting materials. An analytical formula for the power factor is derived based on the one-band model assuming nondegenerate semiconductors to describe quantum effects on the power factor of the low-dimensional semiconductors. The power factor is enhanced for one-and two-dimensional semiconductors when L is smaller than Λ of the semiconductors.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 27 publications
3
120
0
Order By: Relevance
“…By measuring thickness dependent TE properties in InSe, Zeng et al have recently shown that the power factor increases greatly due to the sharper edge of the conduction‐band DOS caused by quantum confinement and a Seebeck coefficient up to 570 µV K −1 in 7 nm InSe sample has been reported. Further analysis shows that power factor in InSe would be increased significantly when the confined dimension is smaller than the thermal de Broglie wavelength, a scenario estimated by theoretical calculation . When the confined length increases beyond than the thermal de Broglie wavelength, the power factor decreases gradually toward the value for bulk InSe, which is shown in Figure .…”
Section: Phonon‐driven Emerging Applications Of 2d Semiconductorsmentioning
confidence: 72%
“…By measuring thickness dependent TE properties in InSe, Zeng et al have recently shown that the power factor increases greatly due to the sharper edge of the conduction‐band DOS caused by quantum confinement and a Seebeck coefficient up to 570 µV K −1 in 7 nm InSe sample has been reported. Further analysis shows that power factor in InSe would be increased significantly when the confined dimension is smaller than the thermal de Broglie wavelength, a scenario estimated by theoretical calculation . When the confined length increases beyond than the thermal de Broglie wavelength, the power factor decreases gradually toward the value for bulk InSe, which is shown in Figure .…”
Section: Phonon‐driven Emerging Applications Of 2d Semiconductorsmentioning
confidence: 72%
“…From the 1990s, the introduction of nanostructures has shown a promising way to independently control S , σ , and κc [1] through quantum confinement effect, and to reduce the lattice thermal conductivity κp due to the phonon-interface scattering [1,32,33,34] for the next generation of high efficiency TE materials. For example, ZT ≈ 2.4 at room temperature has been reported by Venkatasubramanian et al [35] in p -type Bi 2 Te 3 /Sb 2 Te 3 thin film TE materials.…”
Section: Introduction To Thermoelectricitymentioning
confidence: 99%
“…In 2016, Dresselhaus et al proposed that the PF can be dramatically improved by minimizing the quantum well thickness/ λ D ratio in a 2D quantum well system . Thus, we hypothesized that the use of longer λ D should be effective if the carrier electrons are confined within a fixed layer thickness (Figure ).…”
Section: Introductionmentioning
confidence: 83%
“…Hicks and Dresselhaus predicted dramatical enhancements in ZT in 2DES. In semiconductors, 2DES can be realized by quantum well structures in superlattices, and the quantum well structures significantly increase the magnitude of S value due to an increase in the density of states (DOS) near the conduction band edge . This model is based on the assumption that the carrier electrons confined in such a narrow space will not experience reductions in the electrical carrier mobility/conductivity.…”
Section: Introductionmentioning
confidence: 99%